Urbanisation modulates plant-pollinator interactions in invasive vs. native plant species - Buchholz, Sascha (Sci Rep, 2019)
Pollination is a key ecological process, and invasive alien plant species have been shown to significantly affect plant-pollinator interactions. Yet, the role of the environmental context in modulating such processes is understudied. As urbanisation is a major component of global change, being associated with a range of stressors (e.g. heat, pollution, habitat isolation), we tested whether the attractiveness of a common invasive alien plant (Robinia pseudoacacia, black locust) vs. a common native plant (Cytisus scoparius, common broom) for pollinators changes with increasing urbanisation. We exposed blossoms of both species along an urbanisation gradient and quantified different types of pollinator interaction with the flowers. Both species attracted a broad range of pollinators, with significantly more visits for R. pseudoacacia, but without significant differences in numbers of insects that immediately accessed the flowers. However, compared to native Cytisus, more pollinators only hovered in front of flowers of invasive Robinia without visiting those subsequently. The decision rate to enter flowers of the invasive species decreased with increasing urbanisation. This suggests that while invasive Robinia still attracts many pollinators in urban settings attractiveness may decrease with increasing urban stressors. Results indicated future directions to deconstruct the role of different stressors in modulating plant-pollinator interactions, and they have implications for urban development since Robinia can be still considered as a “pollinator-friendly” tree for certain urban settings.